The Influence of Financial Literacy, Financial Technology, Risk Perception, and Locus of Control on Investment Decisions with Education Level as a Moderating Variable in West Kalimantan - Alisa, Alisa; Juniwati, Juniwati; Wendy, Wendy; Giriati, Giriati; Mustaruddin, Mustaruddin (Journal of Applied Management Research, 2024)
Financial literacy encompasses objective knowledge, personal skills, and individual expertise in managing and making personal financial decisions. With the increasing complexity of financial instruments, numerous studies indicate that individuals often lack adequate information and understanding of fundamental financial principles. This study aims to examine the influence of financial literacy, financial technology, risk perception, and locus of control on investment decisions, with education level as a moderating variable. Using a quantitative methodology and purposive sampling method, this study finds that a better understanding of financial literacy, effective use of fintech, appropriate risk perception, and a strong internal locus of control can lead to improved investment decisions. The findings highlight that enhanced financial education and the integration of financial technology are crucial for supporting more effective investment choices, thereby expanding the community’s investment knowledge and skills.